Rubber Blend (ENR25/NBR) Based Pressure-Sensitive Adhesives - Soo, Kai Wai (2017)
In this study, the synthesis and characterization of epoxidized natural rubber (ENR 25)/ acrylonitrile-butadiene rubber (NBR) blend pressure sensitive adhesive (PSA) were presented. The blend ratio of ENR25/NBR was fixed at 0, 20, 40, 60, 80, and 100% of ENR 25 content. The zinc oxide (ZnO) and magnesium oxide (MgO) were used as a reinforcing filler to prepare the composite adhesive. Five different loadings, i.e. 10, 20, 30, 40 and 50 phr filler was used in the adhesive formulation. The benzoyl peroxide (BPO) is used as a crosslinking agent to prepare the crosslinked adhesive. The loading of benzoyl peroxide was varied from 1 to 5 phr. Toluene was used as solvent throughout the study.